Systematic review: Application of lean management in improving service efficiency in hospitals in Indonesia - Sari, Emy Novita; Arso, Septo Pawelas; Jati, Sutopo Patria (International Journal Labs, 2023)
Patient satisfaction is affected by the quality of care provided by hospitals. Background: According to the Indonesian Ministry of Health in 2022, the waiting time in Indonesian hospitals is still far from ideal. Lean can be used as a method to solve this problem. Lean is a systematic approach to eliminate waste and improve efficiency. Lean Hospital aims to improve the quality of patient care by reducing waiting time. This study aims to determine the effect of lean management on the efficiency of hospital services in Indonesia. This study was a systematic review and meta-analysis using the PRISMA diagram. The search for articles was based on the eligibility criteria of the PICO model. P = Hospital Management; I = Hospitals that Implement Lean Management; C = Hospitals that Do Not Implement Lean Management; O = Service Efficiency. The articles used were from 4 databases, namely: Google Scholar, Portal Garuda, PubMed, and Researchgate. With keywords including